Socio-Economic analysis of market oriented beekeeping in Atsbi Wemberta District of Eastern Zone, Tigray Region - Gebreyohannes, M. (Mekelle University, 2010)
This study was initiated to assess the process of beekeeping development and diffusion of improved beekeeping management and evaluate the impact of improved beekeeping on household income, per capita income, changes in capacity development and social issues such as educational expenditure, health improvement, and human capita. The study was based on a representative sample of 200 farm households (99 modern beekeepers and 101 traditional beekeepers) selected using random sampling. To analyze the process of beekeeping development and diffusion of improved beekeeping management and to evaluate the impact of improved beekeeping on household descriptive statistics and matching estimation methods were used respectively. Estimated result of the Heckman regression model indicates there is no selection bias. The descriptive analysis explain due to a number of beekeeping development interventions (i.e. supply of beekeeping materials, training) most modern beekeepers had progressive improvement on the utilization methods and honey handling techniques (i.e. skill improvement) together with their accessories, have been distributed to farmers. The propensity score matching result also indicates that the mean income of modern beekeepers is significantly higher than that of traditional beekeepers. The estimated results for the matching methods showed that the average income gain due to improved beekeeping ranges from 2679 to 2888 Birr per household per annum. The overall average total educational expenditures gain due to improved beekeeping ranged between 79.75 and 90.74 Birr and was significant at 1% level based on the kernel, nearest neighbor, stratified and radius, matching methods. The overall average human capital gain due to improved beekeeping ranged between 82.35 and 98.45 Birr and was significant at 5% level based on the kernel, stratified, radius and nearest neighbor, matching methods. Average per capita income gain due to improved beekeeping ranged between 428.4 and 493.5 Birr and was significant at 1% level based on the stratified, radius, kernel and nearest neighbor matching methods. The results certainly imply that the modern beekeepers had better living status than the traditional beekeepers in the woreda. It is suggested to focus on modern beekeeping development technologies and provision of relevant training as well as technical assistances need to up grade for the improvements in beekeeping production.